Analisis Tingkat Ketahanan Pangan Terhadap Kerawanan Pangan di Kabupaten Jombang Tahun 2015 - Wulandari, Mei; , Ir. H. Taryono, M.Si (2016)
The analysis of food security emphasizes on the presentation of data about the dissemination and dominant factor that influence the level of food security toward food insecurity in Jombang, East Java. The purpose of this research are; (1) analyzing the dissemination of the level of food security toward food insecurity in Jombang regency, and (2) analyzing the dominant factor that influences the level of food security toward food insecurity based on the parameters/indicators of food security which are used. The method used in this research is secondary data analysis method. Secondary data analysis methods consist of secondary data collection methods, data processing method and data analysis methods, including analysis of GIS and statistical analysis. GIS analysis in the form of spatial modeling through quantitative approach toward nine parameters of food security. The parameters that used in the mapping of the level of food security toward food insecurity based on the parameter from FSVA (A Food Security and Vulnerability Atlas) of Indonesia. These parameters consist of the ratio of per capita normative consumption to food production, population living below poverty line, population without access to electricity, villages not accessible by four wheel vehicle, life expectancy, underweight children (< 5 years), population without access to clean water, illiterate population, and population with access to health facilities > 5 km. Statistical analysis method such as multiple linear regression analysis to determine the dominant factor which influence the level of food security toward food insecurity in Jombang. The dissemination of the level of food security toward food insecurity in Jombang regency include, 5 districts into the category of highly food security, 11 districts into the category of food security, 4 districts into the category of quite food security, and 1 district into the category of rather food insecurity. The dominant factor that influences the level of food security toward food insecurity based on nine parameters/indicators of food security which are used, is the parameter of the population living below poverty line.